POLYFUNCTIONALITY OF MODERN RURAL FAMILIES: THEORETICAL AND METHODICAL BASES OF THE STUDY - P. P. Deriugin; O. V. Yarmak; D. M. Serebrov (Дискурс, 2018)
The article reveals the main methodological principles of the analysis of the multifunctional nature of modern rural families in the changing Russian society. The importance of concrete historical approach, taking into account regional peculiarities of living of rural families, consideration of the functions of the family as a social institution and as a small social group, the need to distinguish between functions of rural and urban family are shown. New social challenges that affect the appearance of actual approaches to the study of family functions are presented. The polyfunctionality of the rural family is considered as a necessity to realize the challenges of the external environment and meet the needs of family members.